Baseball Seam Recognition at Different Distances. - Clutter, Mason; Do, Michael-Vu; Zimmerman, Aaron; Fogt, Nick (Optometry & Visual Performance, 2024)
Background: A potential visual cue that baseball batters may use to determine the trajectory of pitched balls is the orientation of the ball's seams. However, a batter may have limited time (130-200 ms) to assess pitch trajectory. The purpose of this study was to determine whether observers could reliably identify the seams on a spinning baseball at distances associated with the early trajectory assessment period. Methods: Baseballs spun with a motor were oriented such that they appeared to have two wide red vertical bands, one central wide red vertical band, or no wide red bands. Sixteen young subjects viewed the rotating baseballs at randomized distances from 10 to 45 feet. At each distance, the three seam patterns were randomly presented three times. Subjects were given unlimited time to identify the number of wide red bands (three-alternative forced-choice). Results: The percentage of correct responses ranged from 98% at 10 feet to 76% at 45 feet from the subject. At 16 feet (the maximum distance at which it was reported that the two wide bands of a two-seam fastball could be seen) and at 10 feet (the maximum distance at which it was reported that the thin red bands of a four-seam fastball could be seen), the predicted percent correct was over 95%. At 29 feet from the batter (the ball's distance 200 ms after a 90 mph pitch is released), the predicted percentage correct was at least 90%. The percentage correct was over 90% for all but the 45-foot distance. Conclusions: Subjects correctly identified the number of wide red seams on the ball well over threshold (67%) at all distances. Assessment of the seam orientation might be useful as a visual cue for a baseball batter to predict pitch trajectory.